Koledarček (MS 160) v ljubljanski Narodni in univerzitetni knjižnici - Golob, Nataša (Zbornik za umetnostno zgodovino (Nova vrsta), 1988)
The folding calendar made of the strip of parchment had hitherto been thought to be a work from the Rhine dating from 1415. The paper shows that it is in fact a manuscript from the Flanders-Brabant area. Some elements suggest that this Flemish-Brabant calendar was produced with some Byzantine model in mind. The similarity with other Flemish manuscripts, the writing and the unusual way in which the years are indicated, suggest that the calendar might have been produced later than it is dated, that is around 1465, but on the basis of the calendar model from the year 1415.
Keywords: iluminirani rokopisi; koledarji; rokopisno slikarstvo; Slovenija